Preparation of power point presentation slideshow in delivering lectures: case in UiTM Pahang - Abd Jabar, Faizan; Ali, Roslina; Abd Jabar, Mashita (University Teknology MARA Pahang, 2011)
There are various teaching techniques used by lecturer while assisting students to better understand the subject taught in class. There is no denying that most lecturers prefer to use written material such as whiteboard, handouts, or projectors as their teaching medium. This study describes experiences and concerns of lecturers in preparing the visual slideshow in delivering lectures among lecturers in UiTM Pahang. There are 100 respondents took part in the survey. Questionnaires were distributed randomly to lecturers regardless of faculty. It is hoped that the findings will be able to facilitate and further enhance the new lecturers in obtaining a better understanding and skills in producing better slide presentation using power point.